Drinking natural water unchangeably is associated with reduced all-cause mortality in elderly people: A longitudinal prospective study from China - Liu, Lu; Zheng, Yi; Ruan, Haiyan; Li, Liying; Zhao, Liming; Zhang, Muxin; Duan, Linjia; He, Sen (Frontiers in Public Health, 2022)
Objective Because of rapid economic growth and followed urban expansion in China, many people drinking natural water had to change their water sources to tap water. We aimed to test the unknown association that whether continued use of natural water for drinking is different from switching to tap water in all-cause mortality risks in elderly people. Methods In total, based on Chinese Longitudinal Healthy Longevity Survey, 26,688 elderly participants drinking natural water from childhood to young-old were included in the final analyses. Associations between whether changing drinking water sources or not and all-cause mortality risk were then estimated by Cox regression models with the use of multiple propensity score methods, and the primary analysis used propensity score matching, with other propensity score methods confirming the robustness of the results. Results Baseline characteristics were fairly well balanced by the three post-randomization methods. During a median follow-up period of 3.00 (IQR: 1.52, 5.73) years, 21,379 deaths were recorded. The primary analysis showed people using natural water unchangeably was associated with a lower risk of all-cause mortality than those switching to tap water in later life (HR: 0.94, 95% CI: 0.91–0.97, p < 0.001). Other propensity score methods, as well as Cox regression analysis without using propensity score methods, showed similar results. Conclusions Among elderly people depending on natural water for drinking from their childhood to young-old in China, continued use of natural water was associated with a lower all-cause mortality risk than conversion to tap water later. Further studies in different countries and populations are needed to verify our conclusions.